2011
DOI: 10.17221/4275-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Linguatula serrata infection among dogs (definitive host) and domestic ruminants (intermediate host) in the North West of Iran

Abstract:  Linguatula serrata is a zoonotic parasite causing visceral and nasopharyngeal linguatulosis in humans. Dog and other canines are the main definitive hosts while most herbivores, including ruminants serve as intermediate hosts for linguatulosis. Human rarely become infected as both final and intermediate hosts. This survey aimed to assess the L. serrata infection rate of dogs and domestic ruminants in North West of Iran. The upper respiratory tract of 97 dogs including 45 females and 52 males and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…However, several studies have been carried out as regards the prevalence of L. serrata infection in animals including, dogs (Meshgi & Asgarian, 2003;Oryan et al, 2008), camels (Pourjafar et al, 2007;Tajik et al, 2007;Shakerian et al, 2008;Oryan et al, 2011), buffaloes (Tajik et al, 2008;Rezaei et al, 2011), sheep Nourollahi Fard et al, 2011), cattle (Hami et al, 2009;Nourollahi Fard et al, 2010a) and goats Nourollahi Fard et al, 2010b) in many parts of Iran, but the incidence of L. serrata in herbivores in western Iran is practically unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have been carried out as regards the prevalence of L. serrata infection in animals including, dogs (Meshgi & Asgarian, 2003;Oryan et al, 2008), camels (Pourjafar et al, 2007;Tajik et al, 2007;Shakerian et al, 2008;Oryan et al, 2011), buffaloes (Tajik et al, 2008;Rezaei et al, 2011), sheep Nourollahi Fard et al, 2011), cattle (Hami et al, 2009;Nourollahi Fard et al, 2010a) and goats Nourollahi Fard et al, 2010b) in many parts of Iran, but the incidence of L. serrata in herbivores in western Iran is practically unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In the first step of examination, the prevalence of L. serrata infection were detected 24.81% (100/403) (Rezaei et al, 2012;Youssefi et al, 2012;Sadeghi-Dehkordi et al, 2014;Kheirabadi et al, 2014), 9-52.5% in sheep (Tavassoli et al, 2007a;Nourollahifard et al, 2011;Youssefi et al, 2012;Sadeghi-Dehkordi et al, 2014;Azizi et al, 2015;Kheirabadi et al, 2015), and 14.8-69.1% in cattle (Tajik et al, 2006;Nourollahifard et al, 2010b;Youssefi and Hadizadeh-Moalem, 2010;Rezaei et al, 2011;Youssefi et al, 2012;Alborzi et al, 2013;Nematollahi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…They also have a higher risk of infection compared to visceral organs (Rezaei et al, 2011;Sadeghi-Dehkordi et al, 2014). Therefore, the present study assessed the prevalence of L. serrata infections in the MLNs of goats, sheep, cattle and buffaloes; the obtained infection rates in the mentioned animals were 26.30%, 18.32%, 14.30%, and 13.19%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…(Beaver et al, 1984;El-Hassan et al, 1991;Lazo et al, 1999;Siavashi et al, 2002). Previous studies in Iran have reported L. serrata infection prevalence rates of 27.8-76.5% in dogs (Meshgi & Asgarian, 2003;Rezaei et al, 2011), 19-68% in goats (Rezaei et al, 2012;Youssefi et al, 2012;Dehkordi et al, 2014), 10.2-52.5% in sheep (Tavassoli et al, 2007b;Fard et al, 2011;Youssefi et al, 2012;Dehkordi et al, 2014), and 14.8-69.1% in cattle (Tajik et al, 2006;Youssefi & Hadizadeh-Moalem, 2010;Youssefi et al, 2012;Alborzi et al, 2013;Nematollahi et al, 2015).…”
Section: Microscopic Findingsmentioning
confidence: 99%